2010
DOI: 10.1289/ehp.0901127
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Meta-Regression to Assess the Shape of the Benzene–Leukemia Exposure–Response Curve

Abstract: BackgroundPrevious evaluations of the shape of the benzene–leukemia exposure–response curve (ERC) were based on a single set or on small sets of human occupational studies. Integrating evidence from all available studies that are of sufficient quality combined with flexible meta-regression models is likely to provide better insight into the functional relation between benzene exposure and risk of leukemia.ObjectivesWe used natural splines in a flexible meta-regression method to assess the shape of the benzene–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
2
37
0
2
Order By: Relevance
“…In an Italian multicenter case-control study no association between exposure to solvents and AML was found (16). Excess risk of AML from benzene exposure could be identifiable already at 10 ppm/year exposure levels according to Vlaanderen et al (8). The estimated cumulative benzene exposure in our study exceeded 13.6 ppm/year for 68 cases and 418 controls (table 3).…”
Section: Discussionsupporting
confidence: 43%
“…In an Italian multicenter case-control study no association between exposure to solvents and AML was found (16). Excess risk of AML from benzene exposure could be identifiable already at 10 ppm/year exposure levels according to Vlaanderen et al (8). The estimated cumulative benzene exposure in our study exceeded 13.6 ppm/year for 68 cases and 418 controls (table 3).…”
Section: Discussionsupporting
confidence: 43%
“…Rappaport et al 39 , por meio da comparação de modelos cinéticos de duas vias metabólicas do benzeno, sugerem maior risco de leucemia em baixos níveis ambientais de exposição. Confirmando essa suposição, Vlaanderen et al 40 realizaram um estudo de metanálise por metarregressão com o objetivo de avaliar a curva dose--resposta benzeno e risco de leucemia, sendo indicado pelo modelo uma forma supralinear da curva dose-resposta na região de baixas doses de exposição ao benzeno. Provavelmente, esse resultado de maior risco de leucemia em baixas doses ocorre pelo benzeno ser mais eficientemente metabolizado em baixas concentrações, aumentando a produção de seus metabólitos reativos, que são hematotóxicos [41][42][43][44] .…”
Section: Discussionunclassified
“…More recent occupational examples can be found for lung cancer and diesel fumes, breast cancer and ethylene oxide, and leukemia and benzene. [6][7][8] nonoccupational examples can be found in cohort studies assessed by Pope et al, 9 and Smith and Peel, 10 where rrs for heart disease attenuate over time with increasing exposure to fine particles (PM 2.5 ) from air pollution or cigarettes.…”
mentioning
confidence: 99%